Issues in the Structuring and Acquisition of an Ontology for Medical Language Understanding - Zweigenbaum, P.; Bachimont, B.; Bouaud, J.; Charlet, J.; Boisvieux, J.-F. (Methods of Information in Medicine, 1995)
Medical natural language understanding basically aims at representing the contents of medical texts in a formal, conceptual representation. The understanding process itself increasingly relies on a body of domain knowledge, generally expressed in the same conceptual formalism. The design of such a conceptual representation is a key knowledge-acquisition issue. When representing knowledge, the most important point is to ensure that the formal exploitation of the knowledge representation conforms to its meaning in the domain. We examined some methodological and theoretical principles to enforce this conformity. These principles result from our experience in MENELAS, a medical language understanding project.
Keywords: Natural Language Understanding; Ontology; Knowledge Acquisition; Knowledge Representation; Conceptual Graphs